Evaluation of Bakery Product Defect at PT. ABC Lampung - Prabowo, Ragil Aji; Satar, Ibdal (Universitas Ahmad Dahlan, 2022)
The purpose of bread quality control is to determine the number of defects in bread during production so that causes and solutions can be found to solve the problem. The control chart method and the Pareto diagram were used to determine the product defect. The Control Chart method aims to determine the control of defective products, whether the production process is still within the control limits or outside the control limits and to find out how to control defective products. This study contributes to investigating the quality control of bakery products at PT. ABC in Lampung. The results obtained after the analysis using the P-Chart control showed that the defect bread data was still within the limits of LCL and UCL. By using the Control Chart method, it shows that the product is still within the control limits. The fishbone diagram method contains several factors that cause defects on the bakery products. These factors include materials, people, machines, and processes. The main factor that is very influential in causing defects in bread is the human factor due to the lack of manpower which causes employees to become tired and lack focus in doing work.